Metastatic melanoma presenting as intravenous tumour thrombus. Issue 6 (30th March 2020) - Nguyen, Jennifer; Clements, Warren; McLean, Catriona; Haydon, Andrew; Moore, Maggie; Yap, Kenneth SK; Mar, Victoria; Shackleton, Mark
Summary: Tumour thrombus is a complication that occurs when a malignancy invades into the vasculature, occluding its lumen. Here, we present a rare case of melanoma tumour thrombus of the great saphenous vein of the left thigh, which was diagnosed on 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography and ultrasound‐guided biopsy, and responded well to immunotherapy with pembrolizumab.